Quality of Public Services - LCA Robin Jonathan (LPPM University 17 Agustus 1945 Samarinda, 2017)
Improving the quality of public services at the local level is very important, the community directly receives and feels the service provided by the local government. This research is to know and analyze the quality of public service at the Department of Manpower and Transmigration of East Kutai Regency. The population of this study are all consumers in East Kutai District who come to the Office of Manpower and Transmigration to obtain services. The assessment of the quality of public services consists of variables Realibility, Responsivenes, Assurance, Emphaty dan Tangibles menggunakan skala Likert; Metode Importance and Performance Analysis (IPA) to compare the gap between appraisal and community expectations; And Cartesian Diagram. The conclusions of the study are: (1) There are 10 sub variables in quadrant B, indicating the consumer is satisfied with the service; (2) There are 3 sub-variables in quadrant A, indicating consumer not yet satisfied at service performance; (3) There are 2 sub variables in quadrant C, indicating consumer not satisfied with importance and service performance; (4) There are 4 sub-variables in quadrant D, indicating consumer satisfaction at service performance; (5) The average value of Service Performance that has been received by consumers is smaller than the value of service expectation. This means that the services provided by the Disnakertrans have not provided satisfaction for consumers and therefore need to improve their performance.